Sistem Informasi ERP (Enterprise Resources Planning) untuk Mendukung Fungsi Bisnis pada PT. Cipta Mandiri Elektrindo - Heru Purwanto; Albertus Agung Raharja (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2019)
The development of information technology that has an impact on behavior and culture in business can be so easy and fast. It becomes a challenge for a company to be able to balance and play an active role in order to compete in the business world. In this study researchers tried to model the ERP concept as the basic foundation of integrated business processes. The usecase and squares diagrams are used as business process modeling. the implementation of software development involving modules, views and controllers reinforced with the LRS design is used to display database connectivity. The basis path test gives results with value 3 is an use of algorithms in low risk categories. Validation testing with valid results becomes a response with fulfilled functional requirements. While the results of testing non-functional requirements related to usability through the calculation of the T test where t hit = 4.580> t 0.05, 9 = 2.265, indicating that the system application is acceptable and influences the efficiency and effectiveness of work.